Long-term biomass removal in grasslands reduces plant and soil phosphorus, increases carbon:phosphorus stoichiometry, but does not lead to microbial phosphorus limitation - Andrea Simpson; David Whitehead; Leo M. Condron; Kate H. Orwin; Keith C. Cameron; Niklas J. Lehto (Agriculture, Ecosystems & Environment, 2026)

Regional conservation genomics: insights and opportunities from northern Australia - Teigan Cremona; Brenton von Takach; Robyn Shaw; Alexander Carey; Bridget Campbell; Skye Cameron; Renee Catullo; Caroline Chong; Saul Cowen; Danielle Edwards; Emilie Ens; Tony Griffiths; et al. (Biodiversity and Conservation, 2025)
Biodiversity conservation in northern Australia is characterised by high endemism, data deficiency, and high Indigenous land tenure and population. The Northern Australia Conservation Genomics Forum brought together experts to explore current genetic research with particular emphasis on integration of genomics within conservation practices. We discuss the regional biodiversity of northern Australia, highlighting the unique biogeographic patterns, known and unknown species diversity, and ongoing threats such as habitat degradation, altered fire regimes, invasive species, and climate change. This article synthesises key themes from the forum, including the current application of genomics in conservation, gaps and areas of need and opportunity to advance species conservation in this sparsely populated, yet iconic region of Australia. We highlight the need to expand collaborative research partnerships across land tenures with Indigenous organisations, pastoralists, government and non-government organisations, which is crucial for the effective study and conservation of the region’s biodiversity. The paper identifies the challenges and opportunities in applying genomic data to conservation strategies and applied management, including species translocations and habitat management, while acknowledging the limitations and gaps in current research and collections. The insights from this forum emphasise the advantages in using genomics to inform conservation decisions, and the need for continued research and collaboration to protect northern Australia’s unique biodiversity.

Warming reduces trophic diversity in high‐latitude food webs - Michelle C. Jackson; Eoin J. O'Gorman; Bruno Gallo; Sarah F. Harpenslager; Kate Randall; Danielle N. Harris; Hannah Prentice; Mark Trimmer; Ian Sanders; Alex J. Dumbrell; Tom C. Cameron; Katrin Layer‐Dobra; et al. (Global Change Biology, 2024)
The physical effects of climate warming have been well documented, but the biological responses are far less well known, especially at the ecosystem level and at large (intercontinental) scales. Global warming over the next century is generally predicted to reduce food web complexity, but this is rarely tested empirically due to the dearth of studies isolating the effects of temperature on complex natural food webs. To overcome this obstacle, we used ‘natural experiments’ across 14 streams in Iceland and Russia, with natural warming of up to 20°C above the coldest stream in each high‐latitude region, where anthropogenic warming is predicted to be especially rapid. Using biomass‐weighted stable isotope data, we found that community isotopic divergence (a universal, taxon‐free measure of trophic diversity) was consistently lower in warmer streams. We also found a clear shift towards greater assimilation of autochthonous carbon, which was driven by increasing dominance of herbivores but without a concomitant increase in algal stocks. Overall, our results support the prediction that higher temperatures will simplify high‐latitude freshwater ecosystems and provide the first mechanistic glimpses of how warming alters energy transfer through food webs at intercontinental scales.

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Conservation prioritisation of genomic diversity to inform management of a declining mammal species - Brenton von Takach; Skye F. Cameron; Teigan Cremona; Mark D.B. Eldridge; Diana O. Fisher; Rosemary Hohnen; Chris J. Jolly; Ella Kelly; Ben L. Phillips; Ian J. Radford; Kate Rick; Peter B.S. Spencer; et al. (Biological Conservation, 2024)

High additions of nitrogen affect plant species-specific differences in the composition of main microbial groups and the uptake of rhizodeposited carbon in a grassland soil - Andrea Leptin; David Whitehead; Kate H. Orwin; Samuel R. McNally; John E. Hunt; Keith C. Cameron; Niklas J. Lehto (Biology and Fertility of Soils, 2022)

Empirical evaluation of multi-trait DNA testing in an apple seedling population - Sushan Ru; Craig Hardner; Kate Evans; Dorrie Main; Patrick A. Carter; Julia Harshman; Paul Sandefur; Daniel Edge-Garza; Cameron Peace (Tree Genetics & Genomes, 2021)

Addressing Marine and Coastal Governance Conflicts at the Interface of Multiple Sectors and Jurisdictions - Manuel Bellanger; Cameron Speir; Fabian Blanchard; Kate Brooks; James R. A. Butler; Scott Crosson; Robert Fonner; Sophie Gourguet; Daniel S. Holland; Sakari Kuikka; Bertrand Le Gallic; Rebecca Lent; et al. (Frontiers in Marine Science, 2020)

Prospects for achieving durable disease resistance with elite fruit quality in apple breeding - Feixiong Luo; Kate Evans; John L. Norelli; Zhiwu Zhang; Cameron Peace (Tree Genetics & Genomes, 2020)

Erratum to: Modelling foetal exposure to maternal smoking using hepatoblasts from pluripotent stem cells - Baltasar Lucendo-Villarin; Panagiotis Filis; Madeleine J. Swortwood; Marilyn A. Huestis; Jose Meseguer-Ripolles; Kate Cameron; John P. Iredale; Peter J. O’Shaughnessy; Paul A. Fowler; David C. Hay (Archives of Toxicology, 2017)

Modelling foetal exposure to maternal smoking using hepatoblasts from pluripotent stem cells - Baltasar Lucendo-Villarin; Panagiotis Filis; Madeleine J. Swortwood; Marilyn A. Huestis; Jose Meseguer-Ripolles; Kate Cameron; John P. Iredale; Peter J. O’Shaughnessy; Paul A. Fowler; David C. Hay (Archives of Toxicology, 2017)

Genetic architecture of apple fruit quality traits following storage and implications for genetic improvement - Craig M. Hardner; Kate Evans; Chris Brien; Fred Bliss; Cameron Peace (Tree Genetics & Genomes, 2016)

Erratum to: Climate change impacts on freshwater fish, coral reefs, and related ecosystem services in the United States - Diana Lane; Russell Jones; David Mills; Cameron Wobus; Richard C. Ready; Robert W. Buddemeier; Eric English; Jeremy Martinich; Kate Shouse; Heather Hosterman (Climatic Change, 2015)

Climate change impacts on freshwater fish, coral reefs, and related ecosystem services in the United States - Diana Lane; Russell Jones; David Mills; Cameron Wobus; Richard C. Ready; Robert W. Buddemeier; Eric English; Jeremy Martinich; Kate Shouse; Heather Hosterman (Climatic Change, 2015)

Current applications, challenges, and perspectives of marker-assisted seedling selection in Rosaceae tree fruit breeding - Sushan Ru; Dorrie Main; Kate Evans; Cameron Peace (Tree Genetics & Genomes, 2015)

Early Events of HIV-1 Infection: Can Signaling be the Next Therapeutic Target? - Kate L. Jones; Redmond P. Smyth; Cândida F. Pereira; Paul U. Cameron; Sharon R. Lewin; Anthony Jaworowski; Johnson Mak (Journal of Neuroimmune Pharmacology, 2011)

Establishing Representative No‐Take Areas in the Great Barrier Reef: Large‐Scale Implementation of Theory on Marine Protected Areas - LEANNE FERNANDES; JON DAY; ADAM LEWIS; SUZANNE SLEGERS; BRIGID KERRIGAN; DAN BREEN; DARREN CAMERON; BELINDA JAGO; JAMES HALL; DAVE LOWE; JAMES INNES; JOHN TANZER; et al. (Conservation Biology, 2005)
The Great Barrier Reef Marine Park, an area almost the size of Japan, has a new network of no‐take areas that significantly improves the protection of biodiversity. The new marine park zoning implements, in a quantitative manner, many of the theoretical design principles discussed in the literature. For example, the new network of no‐take areas has at least 20% protection per “bioregion,” minimum levels of protection for all known habitats and special or unique features, and minimum sizes for no‐take areas of at least 10 or 20 km across at the smallest diameter. Overall, more than 33% of the Great Barrier Reef Marine Park is now in no‐take areas (previously 4.5%). The steps taken leading to this outcome were to clarify to the interested public why the existing level of protection was inadequate; detail the conservation objectives of establishing new no‐take areas; work with relevant and independent experts to define, and contribute to, the best scientific process to deliver on the objectives; describe the biodiversity (e.g., map bioregions); define operational principles needed to achieve the objectives; invite community input on all of the above; gather and layer the data gathered in round‐table discussions; report the degree of achievement of principles for various options of no‐take areas; and determine how to address negative impacts. Some of the key success factors in this case have global relevance and include focusing initial communication on the problem to be addressed; applying the precautionary principle; using independent experts; facilitating input to decision making; conducting extensive and participatory consultation; having an existing marine park that encompassed much of the ecosystem; having legislative power under federal law; developing high‐level support; ensuring agency priority and ownership; and being able to address the issue of displaced fishers.

Human skeletal muscle creatine transporter mRNA and protein expression in healthy, young males and females - Robyn M. Murphy; Rebecca J. Tunstal; Kate A. Mehan; David Cameron-Smith; Michael J. McKenna; Lawrence L. Spriet; Mark Hargreaves; Rodney J. Snow (Molecular and Cellular Biochemistry, 2003)